2006
DOI: 10.1590/s0102-09352006000300013
|View full text |Cite
|
Sign up to set email alerts
|

Indução de estro em cabras da raça Toggenburg com dois diferentes dispositivos intravaginais

Abstract: Indução de estro em cabras da raça Toggenburg com dois diferentes dispositivos intravaginais

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
(16 reference statements)
2
6
0
1
Order By: Relevance
“…The results of Pietroski et al (2013) agreed with that report GR differed when using NM or AI, varying from 60, 50 and 80% by treatment with 60 mg of MAP for 6, 9 or 12 days, plus 37.5 μg of PGF2α and 200 IU eCG, both administered in the lateral-vulvar region. Maffili et al (2006) report that the onset of estrus at 37 h after the device removal did not affect the fertility of goats, confirming the result of the present study, with a total of 35.90 ± 14.37 h SRIOE and the GR (%) average at 30 and 60 days being 77% and 76.7%, respectively. This demonstrated that estrus induction of the estrus with acupoint Hou Hai resulted in GR (%) similar to that with T1 and T3, which used the IM route (Table 2), and as expected for caprine species.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results of Pietroski et al (2013) agreed with that report GR differed when using NM or AI, varying from 60, 50 and 80% by treatment with 60 mg of MAP for 6, 9 or 12 days, plus 37.5 μg of PGF2α and 200 IU eCG, both administered in the lateral-vulvar region. Maffili et al (2006) report that the onset of estrus at 37 h after the device removal did not affect the fertility of goats, confirming the result of the present study, with a total of 35.90 ± 14.37 h SRIOE and the GR (%) average at 30 and 60 days being 77% and 76.7%, respectively. This demonstrated that estrus induction of the estrus with acupoint Hou Hai resulted in GR (%) similar to that with T1 and T3, which used the IM route (Table 2), and as expected for caprine species.…”
Section: Resultssupporting
confidence: 92%
“…Maffili et al (2006) tested the effectiveness of short protocols to induce estrus goats, consisting of 60 mg of MAP and added to PGF2 α and eCG, and 50 μg PGF2 α and 250 IU eCG, and demonstrated 100% estrus rates. Non-parametric data (median ± interquartile).…”
Section: Resultsmentioning
confidence: 99%
“…At ovulation, the mean diameter of the dominant follicle was 7.4 ± 0.1 mm, similar to the size previously reported on Toggenburg goats (7.7 ± 1.3 mm, Maffili et al, 2006), as well as in others breeds such as Serrana (7.1 ± 0.1 mm; Simões et al, 2006), Shiba (7.8 ± 0.2 mm; Medan et al, 2005) and Saanen (6.9 ± 1.8 mm; Maffili et al, 2005). Ultrasography is considered an efficient tool to identify ovarian structures.…”
Section: Resultssupporting
confidence: 88%
“…It was suggested that fertility decreased significantly for animals which came into estrus later than 30 hours after sponge removal (late estrus) (Baril et al, 1993). The duration of estrus was on average 24.9 hours, shorter than the 37 hours obtained in Toggenburg does by Maffili et al (2006), 31 hours in Turkish Saanen goats (in the treatment most similar to ours -sponge + eCG + PGF) (Dogan et al, 2008) and 31 hours in Boer goats (Greyling & Van Der Nest, 2000) and similar (25 hours) to the Alpine breed . This variation can be attributed to differences in breed, nutrition, season, different progestagens, use of gonadotrophins and presence of male after sponge removal and social dominance (Orihuela, 2000;Dogan et al, 2008).…”
Section: Discussionmentioning
confidence: 94%